Cholera in Africa: A Climate Change Crisis - Bezawit Kassahun Bekele; Olivier Uwishema; Lydia Daniel Bisetegn; Antonia Moubarak; Mugeniwayesu Charline; Pacifique Sibomana; Chinyere Vivian Patrick Onyeaka (Journal of Epidemiology and Global Health)
Abstract Background Cholera, an acute diarrheal infection caused by Vibrio cholerae, remains a significant public health concern globally, with 1.4-4.0 million cases and 21,000-143,000 deaths annually. While the disease is endemic in 47 less-developed countries across Africa and Asia, the African continent has been particularly affected, with 19 of 29 countries reporting cases in 2023 being from Africa. Aim To explore the trend of cholera outbreaks in Africa and analyze how climate change has contributed to the spread of the disease in the continent. Methods A review of current cholera outbreaks in Africa, with particular focus on Sudan and Ethiopia as case studies, examining the relationship between climatic factors and cholera transmission. Results Recent outbreaks in Sudan (declared September 26, 2023) resulted in 5,414 suspected cases and 170 deaths (case fatality rate 3.1%) across nine states as of December 5, 2023. In Ethiopia’s Somali region, 772 confirmed cases and 23 deaths were reported within two weeks, with approximately 80% of cases affecting children. Climate factors significantly influence cholera transmission: a 1 °C temperature rise doubled cholera cases in Zanzibar. Both drought conditions, which increase Vibrio cholerae concentration in groundwater, and heavy rainfall periods, which lead to flooding and breakdown of sanitary conditions, contribute to outbreak risks. Conclusions Climate change impacts cholera transmission through rainfall patterns, temperature variations, and extreme weather events. Management recommendations include implementing accurate weather surveillance systems, strategic vaccination programs, flood-proof water supply infrastructure, and community engagement protocols. These interventions should be integrated while considering the growing influence of climate change on disease patterns. Clinical Trial Number Not applicable.